To solve the system of equations:
-
First equation:
\(8x - 4y = -28\)
We can simplify this by dividing the entire equation by 4:
\[ 2x - y = -7 \quad \text{(Equation 1)} \] -
Second equation:
\(2x - 6y = 8\)
We can simplify this by dividing the entire equation by 2:
\[ x - 3y = 4 \quad \text{(Equation 2)} \]
Now we have a simpler system of equations:
- \(2x - y = -7\)
- \(x - 3y = 4\)
Next, we can solve this system using substitution or elimination. Let's use substitution. From Equation 1, we can express \(y\) in terms of \(x\):
\[ y = 2x + 7 \]
Now, substitute \(y\) into Equation 2:
\[ x - 3(2x + 7) = 4 \]
Distributing the \(-3\) gives:
\[ x - 6x - 21 = 4 \]
Combine like terms:
\[ -5x - 21 = 4 \]
Add 21 to both sides:
\[ -5x = 25 \]
Now, divide by \(-5\):
\[ x = -5 \]
Now that we have \(x\), we can find \(y\) using the expression for \(y\):
\[ y = 2(-5) + 7 \]
\[ y = -10 + 7 \]
\[ y = -3 \]
Thus, the solution to the system of equations is:
\((-5, -3)\)
Therefore, the answer is:
\((-5, -3)\)